Moderating Effects of Retail Operations and Hard-Sell Sales Techniques on Salesperson’s Interpersonal Skills and Customer Repurchase Intention - Prathamesh Muzumdar; Ganga Prasad Basyal; Piyush Vyas (Journal of Management Research, 2024)
Salesperson’s interpersonal skills have always played an important role in influencing various stages of customer’s purchase decision. With the increase in retail outlets and merchandisers, retail operations have taken a pivotal role in influencing the salesperson’s sales practices and customer’s purchase decisions. This study tries to examine the influence of retail operations and hard-selling strategies on the relationship between salesperson’s interpersonal skills and customer repurchase intention. Salesperson’s interpersonal skills are the trained and tacit competencies that a salesperson employs to improve customer relationship and sales performance. Many organizations prefer skill training as a strategic approach to increase sales. Though successful in its objective, salesperson’s skill training fails to attract repetitive purchases due to unavoidable extraneous factors. It has become a necessity to understand the role of extraneous factors like retail operations and hard-selling sales strategies on sales performance. This study examines the negative influence of retail operations on the relationship between salesperson’s interpersonal skills and customer repurchase intention. The findings suggest that retail operations significantly moderate the relationship between salesperson’s interpersonal skills and customer repurchase intention. We also find that hard-sell sales techniques play a significant moderating role in negatively influencing customer repurchase intention. This study has important implications for retailers and sales managers.